1999
DOI: 10.1046/j.1440-0952.1999.00713.x
|View full text |Cite
|
Sign up to set email alerts
|

Facies architecture of the felsic lava‐dominated host sequence to the Thalanga massive sulfide deposit, Lower Ordovician, northern Queensland

Abstract: The Thalanga volcanic-hosted massive sulfide deposit occurs in the Cambro-Ordovician Mt Windsor Subprovince in northern Queensland. The orebody comprises steeply dipping, stratiform, sheet-like, polymetallic massive sulfide lenses. Overall, the volcanic facies architecture at Thalanga is dominated by quartz-and/or feldspar-phyric lavas and synvolcanic intrusions that comprise coherent facies and in situ and resedimented autoclastic facies. Systematic phenocryst logging (mineralogy, abundance, size) has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 19 publications
2
14
0
Order By: Relevance
“…This represents several eruptive units (Paulick and McPhie, 1999). Nevertheless, the high positive correlations shown by the rhyolite data in immobile element plots suggest that the footwall rocks of the mine area originally were compositionally relatively uniform.…”
Section: Immobile Componentsmentioning
confidence: 90%
See 3 more Smart Citations
“…This represents several eruptive units (Paulick and McPhie, 1999). Nevertheless, the high positive correlations shown by the rhyolite data in immobile element plots suggest that the footwall rocks of the mine area originally were compositionally relatively uniform.…”
Section: Immobile Componentsmentioning
confidence: 90%
“…Even so, on the basis of a detailed volcanic facies analysis, Paulick and McPhie (1999) found that zones of intense alteration cut across coherent emplacement units with little evidence of control by volcaniclastic permeability, except at West Thalanga. They considered that the pyritic stringer zones may originally have been normal to stratigraphy and were rotated into the present oblique orientation by shearing associated with regional folding.…”
Section: Deposit Geologymentioning
confidence: 99%
See 2 more Smart Citations
“…Allen 1992;McPhie & Allen 1992;Allen et al 1996aAllen et al , 1996bPaulick & McPhie 1999;Soriano & Marti 1999;Gibson et al 1999;Doyle & McPhie 2000;Lafrance et al 2000;Paulick et al 2004;Montelius 2005). Ancient volcanic successions are an important source of information on the character, product and architecture of submarine volcanism, since direct observation of silicic submarine volcanic centres is very limited, and in any case their sub-seafloor structure and facies are concealed.…”
Section: Introductionmentioning
confidence: 99%